Phatic Expression in Daily Conversation at Pt.Smoe Indonesia: Discourse Analysis - Situmorang, Maruli (Pendidikan Bahasa Inggris (Universitas Internasional Batam), 2017)
The writer aimed to find out the way PT. SMOE Indonesia use phatic expression in daily conversation and which type of phatic expression they frequently use. The writer collected data by recording conversation performed by employees and transcribed those conversation into written form. Qualititative method was employed to analyze utterances in daily conversations of employees at PT SMOE Indonesia. The writer also found that 85% phatic expressions used are other-oriented type which means employees tend to give special attention for other. The writer suggests further research with large number of data from several company to examine the use of phatic expression use in daily conversation in Batam.